Optimal Antimicrobial Catheter Lock Solution, Using Different Combinations of Minocycline, EDTA, and 25-Percent Ethanol, Rapidly Eradicates Organisms Embedded in Biofilm - Raad, Issam (American Society for Microbiology, 2007)
Antimicrobial lock solutions may be needed to salvage indwelling catheters in patients requiring continuous intravenous therapy. We determined the activity of minocycline, EDTA, and 25% ethanol, alone or in combination, against methicillin-resistant Staphylococcus aureus and Candida parapsilosis catheter-related bloodstream infection strains in two established models of biofilm colonization. Biofilm-colonized catheter segments from a modified Robbins device and a silicone disk biofilm colonization model were exposed to these antimicrobial agents for 15 or 60 min, respectively. After exposure, segments were sonicated and cultured. To determine regrowth after incubation at 37°C, following the brief exposure to the antimicrobial agents, an equal number of segments were washed, reincubated for 24 h, and then sonicated and cultured. The triple combination of minocycline-EDTA (M-EDTA) in 25% ethanol was the only antimicrobial lock solution that completely eradicated S. aureus and C. parapsilosis in biofilm of all segments tested in the two models, and it completely prevented regrowth. In addition, M-EDTA in 25% ethanol was significantly more effective in rapidly eradicating the growth or regrowth of methicillin-resistant S. aureus and C. parapsilosis biofilm colonization in the two models than the other solutions—minocycline, EDTA, M-EDTA, 25% ethanol, and EDTA in ethanol. We conclude that M-EDTA in 25% ethanol is highly effective at rapidly eradicating S. aureus and C. parapsilosis embedded in biofilm adhering to catheter segments.